Kategoria "moral capital" w etyce społeczno-gospodarczej - Wódka, Marek (Annales. Etyka w Życiu Gospodarczym, 2016)
The theory of human capital is a vital common point of economics and social-economicethics. In the economic literature there are two accounts of human capital.In the first account, the human capital is the human himself, as a creator of goodsand services (A. Smith, J.S. Mill, T.W. Schultz). In the other account, the capitalconsists of the skills, abilities, knowledge, energy and health that the human possesses(D. Begg, J.B. Say, G.S. Becker). In economic ethics, human capital is profoundlyanalysed in relation to economic growth. However, the growth depends notonly on the physical and mental health of businesspersons and employees, their educationand professional skills, but also on their moral development. The categoryof human capital – although it remains quite trendy – gets interpreted in reductionistways, i.e. in economic dimensions only, whereas the human factor in the economyshould be extended to the category of moral capital. These days, the concept ofmoral capital begins to play a very serious role in the foundations of social sciences.The objectives of this paper are: to compare different theories of human capital, toemphasize the need for a comprehensive account of the subject, and to defend a thesisthat moral capital resources support business efficiency.